Comparative Modelling and Prediction of Mutant Structures in TREM2 Protein using Computational Tools (Journal of Pharmaceutical Negative Results, 2022)
Aim. Comparative modelling of mutant structures of TREM2 associated with Alzeihmers disease using Homology modelling,Fold recognition and Novel Ab Initio methods.Materials and Methods. The sample size of 10 most deleterious mutations of TREM2 resulted previously by PROVEAN and PredictSNP was modelled using Bioinformatic computational tools such as SWISS model,Pyre2,tr Rosetta.Results. The best mutant model with 99.36% of identity and 99.72% ramachandran plot resulted by SWISS model is S116C.Most accurate mutants modelled by Pyre 2 are S116C,R98W,D39G,R6C,A105V all with 100% confidence in modelled structure and 50% of coverage.The perfect match score (i.e.Estimated TM score )between two structures was shown by S31F which was the result of tr Rosetta. Conclusion. The best modelled mutant structures has been predicted by using Comparative modelling, Fold recognition, Novel Ab intio methods.